PENCARIAN JATI DIRI (SELF-DISCOVERY) MILKMAN DALAM SONG OF SOLOMON KARYA TONY MORRISON: Self-discovery, Conflict, Gold, Family root - Erwanto, Lambang (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2010)
Self-Discovery is needed by everyone in order to give self- respect. The one who lost him/herself can not be proud of his/her life. The person will have no hope and purpose in his/her life. It is happened to Milkman. His life is such a disgrace for him and his family until someday he decided to take a travel to Danville. His traveling is a trip to find out who he is. Finally, his journey give him a benefit for himself and his family. He can find his family root; his great grand father is a legend because he can fly without wings like a bird; his name, Solomon, becomes famous. His discovery completes his life in the world.